Modeling And Analysis Mechanisms of Electrical Energy Generated By Power Sea Wave Type of Piezoelectric Rowboat - Wiwiek Hendrowati; Moch Solichin; Harus Laksana Guntur (JMES The International Journal of Mechanical Engineering and Sciences, 2017)
The availability of electricity in the middle of the sea is important for lighting the fishing boat. Therefore, it was designed on a rowboat mechanism associated with piezoelectric energy as the converter. This study simulates the movement of ocean waves with the frequency and amplitude variations that will produce different force. The force of moving components in the mechanism which further encourages piezoelectric cantilever. Deflection caused by the piezoelectric cantilever will produce electrical energy. The greater of the wave frequency, the greater displacement and velocity of  thrustmass, so that electric power generated also increases. When the greater the number of Piezoelectric used, the electrical energy produced is getting smaller. This is due to the increasing number of hard piezoelectric added to be deflected. In this study, the maximum electrical energy produces the highest frequency, high amplitude and the number of piezoelectric slightly.